Criminal law characteristics of mass destruction weapons as a criminal offense constructive objective feature (Articles 439, 440 of the Criminal Code of Ukraine) - О. V. Shamsutdinov (Law and Safety)
The norms of international and national legislation, which determine the definition and meaning of the concept of mass destruction weapons, as well as each of its components – chemical, biological (in particular, toxin) and nuclear weapons – have been studied. It has been established that a constructive objective feature of the crimes provided for in Articles 439 and 440 of the Criminal Code of Ukraine is not any weapon of mass destruction, but only those prohibited by international treaties, the consent of which is binding on the Verkhovna Rada of Ukraine. Considering that the highest body of the legislative power of Ukraine has not ratified the international treaty on the prohibition of nuclear weapons, approved by the General Assembly of the United Nations on July 7, 2017, the position of the scientists who believe that as part of the crime of “use of mass destruction weapons” (Article 439 of the Criminal Code of Ukraine), nuclear weapons are not part of the concept of “weapons of mass destruction” has been supported.